Recent advances in management of transient ischaemic attacks and minor ischaemic strokes. - Rothwell, P; Buchan, A; Johnston, S (2006)
The risk of recurrent stroke during the first few days after a transient ischaemic attack or minor stroke is much higher than previously estimated. However, there is substantial variation worldwide in how patients with suspected transient ischaemic attack or minor stroke are investigated and treated in the acute phase: some health-care systems provide immediate emergency inpatient care and others provide non-emergency outpatient clinical assessment. This review considers what is known about the early prognosis after transient ischaemic attack and minor ischaemic stroke, what factors identify individuals at particularly high early risk of stroke, and what evidence there is that urgent preventive treatment is likely to be effective in reducing the early risk of stroke.